INTEGRASI TANGGUNG JAWAB SOSIAL DALAM BISNIS BERBASIS NILAI-NILAI PENDIDIKAN ISLAM “INTEGRATION OF SOCIAL RESPONSIBILITY IN BUSINESS BASED ON ISLAMIC EDUCATIONAL VALUES” - Elawati, Elawati; Kamila, Siti Khafidatul; Ulum, Siti Raudathul; Maryati, Sulis (Sindoro: Cendikia Pendidikan, 2024)
Social responsibility in Islam teaches a balance between rights and obligations towards oneself, society, and the environment, emphasizing values ​​such as justice, honesty, and kindness. In the business context, Islamic values ​​play an important role in forming companies that focus not only on profit, but also on social and environmental welfare through social responsibility practices that are in accordance with sharia, such as avoiding usury and gharar. Islamic education plays a vital role in forming socially responsible entrepreneurs, by instilling fair business ethics, collective welfare, and sharia economic principles. However, challenges such as limited understanding of sharia economics and limited infrastructure support can hinder the implementation of these values ​​in the business world, so Islamic education is expected to strengthen entrepreneurs' commitment to ethical principles in a competitive environment.